Hypodematium shingii sp. nov. (Hypodematiaceae; Polypodiales): Replacing the misapplied “H. crenatum”, a widespread fern from Asia - Fan, Xue-Ping; Zhang, Liang; Knapp, Ralf; He, Hai; Gao, Xin-Fen; Zhang, Li-Bing (Phytotaxa, 2021)
Hypodematium shingii (Hypodematiaceae), a new fern species, is described and illustrated from limestone regions in southern China and Southeast Asia. Hypodematium shingii is different from true H. crenatum in morphology and distribution.